2019
DOI: 10.3171/2019.2.focus18725
|View full text |Cite
|
Sign up to set email alerts
|

Decompression of lumbar canal stenosis with a bilateral interlaminar versus classic laminectomy technique: a prospective randomized study

Abstract: OBJECTIVEThe aim of this study was to compare the radiological and clinical results of bilateral interlaminar canal decompression and classic laminectomy in lumbar canal stenosis (LCS).METHODSTwo hundred eighteen patients with LCS were randomized to surgical treatment with classic laminectomy (group 1) or bilateral interlaminar canal decompression (group 2). Low-back and leg pain were evaluated according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
0
18
1
Order By: Relevance
“… 48 50 A recent study compared the radiological and clinical results of bilateral interlaminar decompression and laminectomy. 51 However, this study was a single-centre study, was not blinded, and did not include a computerised randomisation. Furthermore, there were no data regarding the cost-effectiveness of both surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“… 48 50 A recent study compared the radiological and clinical results of bilateral interlaminar decompression and laminectomy. 51 However, this study was a single-centre study, was not blinded, and did not include a computerised randomisation. Furthermore, there were no data regarding the cost-effectiveness of both surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-four articles were retained for a comprehensive evaluation. Finally, 14 trials including 1,106 participants were included in the final analysis (5)(6)(7)(8)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Supplementary Table S4 showed characteristics of the included trials and participants.…”
Section: Systematic Review and Qualitative Assessmentmentioning
confidence: 99%
“…Wide resection of bone, ligament, and muscle structures results in increased postoperative pain, blood loss, complications, and length of hospital stay ( 5 , 6 ). Recently, a number of experts have recommended surgical techniques that preserve posterior midline structures ( 5 , 7 , 8 ). Removal of midline structures may lead to postoperative spinal instability ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The development of endoscopic surgery in lumbar decompression also has become practical choice for decompression in herniated nucleus pulposus (HNP) as well as in degenerative lumbar canal stenosis (LCS), with various techniques being adopted to address underlying pathologies (uniportal vs. biportal, unilateral vs. bilateral decompression) [7], [8], [9]. A prospective study by Soliman and Ali [10] compares the outcome of LCS surgery using minimally invasive decompression with microscope and the conventional open laminectomy. They found that MD permits safe and acceptable spinal canal decompression in patients with LCS.…”
Section: Introductionmentioning
confidence: 99%